Legal Review of the Criminal Act of Human Trafficking of Minors - Panggabean, Grace Margaretha Br; Sulistyawati, Sri; Ardini, Aida (International Journal of Business, Law, and Education, 2024)
This research is motivated by trafficking activities, which are often used for sexual exploitation purposes and for work in rough places that provide low wages. According to internal reports, trafficking is a significant problem in Indonesia. Many children are exploited in domestic slavery, commercial sexual exploitation, rural agriculture, mining, and fisheries. Victims are initially recruited with sweet promises and are eventually forced to become prostitutes. The legal research method used in this study is normative juridical research, which is research conducted or aimed only at written regulations with the nature of descriptive-analytical research, which is a method that functions to describe or provide an overview of the object being studied. The data source used is secondary data with qualitative data analysis. The results of this study show that The main factor in the rampant trafficking of women and children is poverty; they try to improve the economy by looking for work. However, their dream of finding work is not as easy as imagined because of the bitter suffering they get. Instead of getting a job, they are being bought and sold. Efforts to prevent the crime of human trafficking or trafficking can be made in several ways, namely improving community education, especially alternative education for girls, including educational facilities and infrastructure.